Stemming javanese affix words using nazief and adriani modifications - Aji Prasetya Wibawa; Felix Andika Dwiyanto; Ilham Ari Elbaith Zaeni; Rizal Kholif Nurrohman; AN Afandi (Jurnal Informatika, 2020)
Stemming is the process of finding a basic word with several stages of affix removal. The main reason for stemming is to check spelling and machine translation and to support the effectiveness of the retrieval process. This study uses the Nazief and Adriani algorithm for stemming Javanese-influenced words. The first step taken is data collection and making a basic word dictionary. Then do the stemming process. Before stemming, modifications are made to the rules. The rules of the Nazief and Adriani algorithm, which are based on the morphology rules of the Indonesian language, are modified to suit the morphological rules of the Javanese language. Of the 366 words that were tested, it produced 351 correct basic words and 15 basic words that experienced errors. The results show that this algorithm can be used for stemming Javanese with an accuracy value of 95.9%.